Assessment of Self Medication Practice and Drugs Storage Among South Sudanese Community in Addis Ababa, Ethiopia - Achuil Christo; Bekele Anbessa (Journal of Advanced Pharmaceutical Science And Technology, 2020)
Background Self-medication (SM) can be defined as the use of drugs to treat self-diagnosed disorders or symptoms, or the intermittent or continued use of a prescribed drug for chronic or recurrent disease or symptoms. A number of individuals in developing countries do not attend physicians for their illnesses; instead they commonly use self-medication. Self-medication could be using drugs existing in home like over the counter (OCT) drugs, traditional medicine, prescription only drug. Self-medication is not always bad, hence for the over the counter drugs it is beneficial. Inappropriate storage and use of medicines at home could have a direct influence on public health, the environment and the health-care services and it increases the risk of self-medication. Objective To assess the practice of self-medication and drug storage among South Sudanese community in Addis Ababa. Materials and Methods A cross sectional study design was conducted in Addis Ababa city from April 22 to April 26/2019. Data was collected by semi structure-questionnaire consisting questions on general demographic, socio-economic as well as on perceived illness/ symptoms in the past four weeks and actions taken for it. The data collected was screened before it is analyzed. Data analysis was done by using calculator. Results From the total 297 respondents 286 (96.2%) had reported self-medication in the last one month before the study period. The most common types of ailments for which the respondents reported to have practiced self-medication were cough, cold and sore throat 90(30.3%), followed by headache 66(22.2%), diarrhea 52(17.5%) ,abdominal pain 47(15.8%), fever 21(7.07%) and vomiting 10(3.3%). The reasons given for self-medication were; the illness was minor 226(76%) and previous experiences with similar ailments 31 (10.4%) were found to be the two major reasons given by the respondents for self-medication in this study. The majority of the respondents 242(81.4%) who practiced self-medication obtained information on self-medication from friends and 29(9.7%) obtained information from family members. The most frequently used group of drugs used for self-medication were analgesics/antipyretics 177(59.5%) and antimicrobial which account 75(25.2%) each followed by antihelmenthics 24(8.08%).The main source of drugs for SM was in pharmacy 220(74.07%) followed by leftover drugs 41(13.8%) while drug retail outlet, and neighbors and relatives were the suppliers to 12.13% respondents each. Conclusion and Recommendation A significant number of respondents (96.2%) use S/M from those perceived illness. Majority of the self-medicated individuals used due to minor illness. The most common category of drugs used was analgesics/antipyretics and antimicrobials. And the reason reported for using S/M was minor illness and previous experience with the illness. Most of respondents obtained drugs easily from pharmacy. So, pharmacies are the major sources of drugs used for S/M. The increased of drugs storage to treat similar illness/symptom and drugs left over from previous use contribute to the increase in the S/M practice. Common drugs store reported by respondents who store modern drugs were analgesic/antipyretic. Most of the respondents stored the drug in locked cabinets. A lot is need to be done in educating the public including the health care providers on the type of illnesses that can be self-diagnosed and self-treated, the type of drugs to be used for S/M, and the proper use of drugs. During dispensing of drugs emphasis should be given to all drug consumers and dispenser because of resistance and side effects of drug is the main challenging problem even in the world. Food, Medicines and Healthcare Administration and Control Authority (FMHACA) needs to effectively implement laws on drug handling and dispensing so as to take necessary measures on illegal providers of drugs.
Keywords: Self-medication